Microalbuminuria and Hypertension in Pregnancy: Role of Aldosterone and Inflammation. Issue 9 (31st May 2013) - Armanini, Decio; Ambrosini, Guido; Sabbadin, Chiara; Donà, Gabriella; Clari, Giulio; Bordin, Luciana
Abstract : Women with a history of hypertension in pregnancy are at increased risk of microalbuminuria later in life. Microalbuminuria is a marker of kidney dysfunction frequently related to an inflammatory event. Pregnancy is a dynamic process characterized by immune tolerance, angiogenesis, and hormonal regulation. Menstruation and pregnancy are associated with a physiological inflammation, which is altered in preeclampsia and probably in other hypertensive situations of pregnancy. An imbalance between pro‐oxidant factors and the ability to scavenge these factors produces oxidative stress, which has been evaluated in many cells, but leukocytes are the main source of inflammatory cytokines and experimental and clinical evidence support a possible role of aldosterone as a mediator of placental and renal damage mediated by growth factors, reactive oxygen species, and cytokines. Angiotensin‐converting enzyme inhibitors and aldosterone receptor blockers are frequently effective in reducing the risk of progression of cardiovascular and renal disease.